Markets for heterogeneous products: A boundedly rational consumer model - Marco Valente (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2009)
The paper is based on the acknowledgement that properties of markets stemming from features of demand are too frequently overlooked in the economic literature, and a re-balancing is necessary to properly account for theoretical and empirical phenomena. We sustain that one of the most relevant reasons for the neglect of the role of demand is the lack of an adequate representation of consumers. This claim is particularly relevant for evolutionary economics since its critique to the mainstream approach stopped at the representation of firms. The standard utility maximization approach to consumers' theory is even less defensible than the related assumption of producers' rationality, given the lack of competitive pressure on consumers. As a contribution to this theoretical gap, the paper presents a model for consumer based on the assumption of bounded rationality and inspired to the literature on experimental psychology. The proposed model can be applied to multi-dimensional products/services and relies on intuitive and potentially observable parameters, allowing for a wide range of theoretical and empirical applications. Moreover, the intrinsic structure of the model provides a clear definition of preferences, meant as ex-ante decisional criteria, distinguished from post-hoc justification of any decisional result. Though structurally simple, the proposed model is very flexible and allows for a clear exploration of the impact of specific demand features on the produced results. Several experiments show that the model can be successfully applied both to generate standard results and to implement complex configurations such as those of generated by large markets with heterogeneous products. Among the results presented, the most relevant concerns the identification of two classes of market segmentation, generated by the identical suppliers and demand's exogenous factors, but different consumers' decisional mechanisms. The results produced are observationally equivalent, but are shown to have radically different properties, and are proposed as initial elements of a taxonomy for the classification demand classes, likely to explain common properties across different markets.
Keywords: C63; D11; D81; L10; L15; M30; 330; Evolutionary Economics; Consumer Theory; Bounded Rationality; Marketing and Preferences; Simulation Models; Market Structure